The Linguocultural and Linguocognitive-pragmatic Approaches to Studying Proverbs and Sayings - Shalunts, Nare (Bulletin of Yerevan University B: Philology, 2025)
The article explores academic approaches to linguoculture, focusing on the interrelations among thought, cognition, and discourse. Specifically, proverbs and sayings are unique expressions of linguoculture, grounded in social cognition. They encompass the distinctive features of linguoculture and function as a means of preserving linguocultural memory. From the perspective of the pragmatic properties of proverbs, the importance of cognitive processes is emphasized. In this context, the significant role of the communicative function of proverbs in discourse should be noted, along with the manifestations of the general and the individual. In light of these considerations, the study of proverbs and sayings at the intersection of linguocultural and linguocognitive-pragmatic perspectives is highly relevant within the framework of contemporary linguistics. Proverbs and sayings are thus studied at the crossroads of categories such as language, culture, cognition and discourse.
Keywords: proverb; saying; proverbial discourse; linguoculture; cognitive process; linguopragmatics